2016
DOI: 10.3390/su8080710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Straw Incorporation on Soil Nutrients, Enzymes, and Aggregate Stability in Tobacco Fields of China

Abstract: Abstract:To determine the effects of straw incorporation on soil nutrients, enzyme activity, and aggregates in tobacco fields, we conducted experiments with different amounts of wheat and maize straw in Zhucheng area of southeast Shandong province for three years (2010)(2011)(2012). In the final year of experiment (2012), straw incorporation increased soil organic carbon (SOC) and related parameters, and improved soil enzyme activity proportionally with the amount of straw added, except for catalase when maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 53 publications
5
32
0
Order By: Relevance
“…A highly significant correlation (p < 0.01) between the aggregate fraction (>5 mm) and DSA WSA, MWD, and GMD was observed, in contrast to other size fractions and related soil properties (Table 6). The results of present study are aligned with the published papers [36,52,64,65]. Soil organic matter is the key compound affected by a range of microbial activities (living and dead organisms, decomposable SOM, and dead plant materials).…”
Section: Relationship Between Soil Aggregates (Dsa and Wsa) And Soil supporting
confidence: 73%
“…A highly significant correlation (p < 0.01) between the aggregate fraction (>5 mm) and DSA WSA, MWD, and GMD was observed, in contrast to other size fractions and related soil properties (Table 6). The results of present study are aligned with the published papers [36,52,64,65]. Soil organic matter is the key compound affected by a range of microbial activities (living and dead organisms, decomposable SOM, and dead plant materials).…”
Section: Relationship Between Soil Aggregates (Dsa and Wsa) And Soil supporting
confidence: 73%
“…Evazi et al, (2003) reported that soil enzymatic activities (acid and alkaline phosphatases, alpha-glucosidase, arylsulfatase and urease) were higher in continuous corn under no tillage than conventionally tilled soil. Zhang et al, (2016) observed that activity of the enzymes (urease and sucrase) increased with the amount of straw applied. Incorporation of maize straw was more effective to increase enzyme activities as compared with wheat straw incorporation because of narrow C: N ratio of maize straw than wheat straw which facilitates faster decomposition of maize straw.…”
Section: Urease and Amidohydrolases Activitymentioning
confidence: 91%
“…Most often, improvements in aggregate stability were associated with an increase in soil organic carbon content [17][18][19]. Many studies have shown that organic amendments (e.g., manure and crop residues) to soil over time not only could maintain or increase soil fertility and SOC accumulation but also improve aggregation [6,14,[20][21][22][23]. Other workers, however, reported that SOC content and soil structure declined following the continuous application of mineral fertilizer alone [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, weaker correlations have been described between wateror acid-extractable C fractions and aggregate stability. Apart from SOC and its fractions, other soil characteristics such as sesquioxides, texture, and exchangeable cations are involved in soil aggregation and stabilization [19][20][21]35,36]. For instance, macro-aggregates in red soil tended to increase with the accumulation of SOC and Fe-oxides following the application of manure plus nitrogen fertilizer [37].…”
Section: Introductionmentioning
confidence: 99%